Evaluation of Interface Shear Strength Properties of Geogrid Reinforced Foamed Recycled Glass Using a Large-Scale Direct Shear Testing Apparatus - Arul Arulrajah; Suksun Horpibulsuk; Farshid Maghoolpilehrood; Wisanukorn Samingthong; Yan-Jun Du; Shui-Long Shen (Advances in Materials Science and Engineering)
The interface shear strength properties of geogrid reinforced recycled foamed glass (FG) were determined using a large-scale direct shear test (DST) apparatus. Triaxial geogrid was used as a geogrid reinforcement. The geogrid increases the confinement of FG particles during shear; consequently the geogrid reinforced FG exhibits smaller vertical displacement and dilatancy ratio than FG at the same normal stress. The failure envelope of geogrid reinforced FG, at peak and critical states, coincides and yields a unique linear line possibly attributed to the crushing of FG particles and the rearrangement of crushed FG after peak shear state. The interface shear strength coefficient α is approximately constant at 0.9. This value can be used as the interface parameter for designing a reinforced embankment and mechanically stabilized earth (MSE) wall when FG is used as a lightweight backfill and triaxial geogrid is used as an extensible earth reinforcement. This research will enable FG, recently assessed as suitable for lightweight backfills, to be used together with geogrids in a sustainable manner as a lightweight MSE wall. The geogrid carries tensile forces, while FG reduces bearing stresses imposed on the in situ soil. The use of geogrid reinforced FG is thus significant from engineering, economical, and environmental perspectives.